Effect of fixed and self-suggested rest intervals between sets of resistance exercise on post-exercise cardiovascular behavior - Karla Fabiana Goessler; Marcos Doederlein Polito (Revista Brasileira de Cineantropometria e Desempenho Humano, 2013)
This study aimed to compare differences in the number of repetitions after exercises with different rest intervals and to analyze cardiovascular parameters after resistance training. The sample comprised 10 physically activemen (23±2 years). The one-repetition maximum (1RM) test was performed in the following order: bench press, guided squat bar, biceps curl and leg curl. After the 1RM test, the individual held three sessions of resistance training, on different days, with rest intervals of 1 minute, 2 minutes, and self-suggested intervals, randomized for each day. We calculated 75% of the load of the 1RM test, with three series of maximum repetitions performed to exhaustion. Cardiovascular variables were measured at rest and during 30 minutes after exercise. In the self-suggested interval, which showed an average time of rest(157±37 seconds) similar to the 2-minute interval, more repetitions were performed compared to the 1-minute interval session, with no difference in relation to the 2 minute-interval session. No difference was found in systolic blood pressure and in the high frequency (HF) component between the intervals, but post-exercise hypotension was observed in diastolic blood pressure after 10 minutes’ recovery in all intervals, with a longer duration in the 2-minute interval session. After 30 minutes’ recovery, an increase in the low frequency (LF) component was registered for the 2-minute interval session, and anincrease in LF/HF was found at 10, 20 and 30 minutes of recovery after sessions with 1- and 2-minute intervals, demonstrating a possible predominance of sympathetic action. The self-suggested interval did not show changes in the components of heart rate variability. These findings suggest that intervals of at least 2 minutes between sets may be interesting to provide more repetitions and reduce the post-exercise sympathetic effect.